El control de convencionalidad a través del control concreto de constitucionalidad en el ecuador - Durango , Rodrigo (2016)
The Interamerican Court of Human Rights has been prolific to seek mechanisms for greater protection of human rights on the continent. One of them is called conventionality control, which aims to cohere domestic law with the American Convention on Human Rights, so that the domestic legal provisions do not conflict with this international instrument. This legal mechanism has not been free of criticism. In Ecuador it is necessary to determine the procedural instrument that judges have to perform the conventionality control that is consistent with the Ecuadorian legal system. This paper aims to demonstrate that concrete control of constitutionality is the procedural mechanism by which the Ecuadorian judges must perform control of conventionality